CORPORATE MANAGEMENT IN THE NEW ECONOMY OF ROMANIA - Maria, GÂF-DEAC (Strategii Manageriale)
The paper deals with corporate management which is the set of processes and systems implemented to organize, direct and control firms, with the objective of increasing their value and performance or eliminate barriers and obstacles to development. In fact, there is a concentration of attention on the efficient management systems, the concern being found on improving business board of directors, leading the company to operational non-sustainability. It concludes that, in fact, the worst situation is seen when officials from outside partners (strategic investors) can not understand how far advanced the classic structure of local economic interests, to what kind of market economy is heading Romania, as this framework does not feel attracted to develop business and significant investment in modernization.